Small molecule Z363 co‐regulates TAF10 and MYC via the E3 ligase TRIP12 to suppress tumour growth. Issue 1 (13th January 2023) - Xiong, Yan; Wang, Lulu; Xu, Shiyao; Fu, Beibei; Che, Yuchen; Zaky, Mohamed Y.; Tian, Rong; Yao, Rui; Guo, Dong; Sha, Zhou; Lin, Feng; Lin, Xiaoyuan; et al.
Abstract: Background: The MYC oncoprotein, also known as the master regulator of genes, is a transcription factor that regulates numerous physiological processes, including cell cycle control, apoptosis, protein synthesis and cell adhesion, among others. MYC is overexpressed in approximately 70% of human cancers. Given its pervasive role in cancer biology, MYC down‐regulation has become an attractive cancer treatment strategy. Methods: The CRISPR/Cas9 method was used to produce KO cell models. Western blot was used to analyzed the expressions of MYC and TATA‐binding proteinassociated factors 10 (TAF10) in cancer cells (MCF7, A549, HepG2 cells) Cell culture studies were performed to determine the mechanisms by which small molecules (Z363119456, Z363) affects MYC and TAF10 expressions and functions. Mouse studies were carried out to investigate the impact of Z363 regulation on tumor growth. Results: Z363 activate Thyroid hormone Receptor‐interacting Protein 12 (TRIP12), which phosphorylates MYC at Thr58, resulting in MYC ubiquitination and degradation and thereby regulating MYC target genes. Importantly, TRIP12 also induces TAF10 degradation, which reduces MYC protein levels. TRIP12, an E3 ligase, controls MYC levels both directly and indirectly by inhibiting MYC or TAF10 activity. Conclusions: In summary, these results demonstrate the anti‐cancer properties of Z363, a small molecule that is co‐regulated by TAF10 and MYC. Abstract : Z363 exerts an anti‐cancer effect on cancer cell and xenograft models by co‐regulating TAF10 and MYC. TRIP12 plays an important role in Z363‐induced cancer cell apoptosis by directly and indirectly inhibiting MYC activity. Z363 promotes MYC ubiquitination by activating its phosphorylation. Z363 induces TAF10 degradation, which reduces MYC protein levels.